Expressive Art Therapy Psychoeducation Module for Mental Health, Resilience, Attitude Towards Seeking Counselling Among Trainee Teachers - Siti NurulHida Abdul Rahman; Mohd Izwan Mahmud; Ku Suhaila Ku Johari; Salleh Amat (Qubahan Academic Journal)
Expressive art therapy helps to reduce psychological problems, develop a more positive view of different social classes (including children, adults and the elderly) and strengthen resilience. This study investigates the feasibility of implementing the psychoeducational module "Expressive Art Therapy" in student teachers. Seven students enrolled in the preparation programme participated in this study. Study participants are required to provide feedback on each activity in which they participate, including suggestions for improvement and testimonials. The results of this study help the researcher to identify shortcomings in the activities in terms of time, resources and instructions and to make improvements in order to develop a high quality module. This research also contributes to theories and methods that the Institute of Teacher Education can use to improve its counselling and psychological services.